PENGARUH FAKTOR-FAKTOR FUNDAMENTAL TERHADAP NILAI PERUSAHAAN - LATUAMURY, SHERLIE EVABIONI (ISAS, 2022)
This research was conducted with the aim of empirically testing the effect of investment decisions, funding decisions and profitability on company value for the period 2018 - 2021. The research area was carried out in real estate and property companies listed on the Indonesia Stock Exchange. The type of data used is secondary data in the form of financial reports of Real Estate and Property companies that Go Public on the Indonesia Stock Exchange (IDX) during the period 2018 to 2021. The data used are published financial reports. The data was obtained from the IDX website: www.idx.id published in 2018 – 2021. The analytical method used is descriptive statistical analysis and classical assumption tests. The analytical method used to test the hypothesis is multiple linear regression analysis. The results of the study show that investment decisions have no effect on firm value, this is evidenced by the value of t = -0.371 with a significance of 0.711 > of error tolerance = 0.05. Funding decisions have an effect on firm value, this is evidenced by the value of t = 2.101 with a significance of 0.038 < of the error tolerance = 0.05. While profitability affects firm value, this is evidenced by the value of t = -3.535 with a significance of 0.001 < of error tolerance = 0.05. Simultaneously investment decisions, funding decisions, and profitability affect firm value, seen from the value of F = 7.206 with a significance of 0.000. The R2 test results in this study were also obtained at 0.197. This shows 0.197. This shows that firm value is influenced by investment decisions, funding decisions and profitability by 19.7% while the remaining 80.3% is influenced by other factors not examined in this study. Keywords: Investment Decision, Funding Decision, Profitability and Value Company.